Legal Protection For Instant Coconut Milk Consumer - Wikan Tri Restu Yanuarti; Kendy Lukianto Kusumohadi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
Consumer protection is a fairly new thing in the laws and regulations in Indonesia. Despite the call for the need of comprehensive legislation for consumers has been socialized for a long time, it was only on April 20, 1999 the government of the Republic of Indonesia issued and enacted Law Number 8 of 1999 concerning Consumer Protection (hereinafter referred to as the Consumer Protection Act) . This study aims to describe a number of things, which include the legality of food additives in instant coconut milk circulating in Indonesia, as well as understanding the legal liability of businessmen of instant coconut milk products containing food additives that exceed the threshold. The results of data analysis are obtained as follows. First, according to Law Number 7 of 1996 concerning Food, it is regulated about food / food additives, including: Article 10 Paragraph (1): Every person who produces food for distribution is prohibited from using any material as food additive which is declared prohibited or exceed the maximum limit set. Food Additives may be used in the production of instant coconut milk, except that the level of use must not exceed the threshold set by BPOM. Article 11 also states: ... Materials that will be used as food additives, but whose impacts on human health are not yet known, must first be examined for security, and their use in food production activities or processes for distribution is carried out after obtaining approval from the government. Second, the legal liability of business actors who use food additives that exceed the threshold can be requested for litigation, both by conducting criminal and civil claims. Or resolved beyond litigation with a pattern of mediation, arbitration and conciliation.